Denmark : Financial Sector Assessment Program-Technical Note-Banking Regulation and Supervision. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2020)
COVID-19 pandemic: The Financial Sector Assessment Program (FSAP) work was conducted prior to the COVID-19 pandemic, so this Technical Note (TN) does not assess the impact of the crisis or the recent crisis-related policy measures. Nonetheless, given the FSAP's focus on vulnerabilities and policy frameworks, the findings and recommendations of the TN remain pertinent. The Danish Financial Supervisory Authority (DFSA) has improved standards in its oversight of banking and insurance sectors since the last FSAP. Nevertheless, risks persist, both in traditional forms, and new areas, such as cyber risk, AML, and innovative market entrants. This note, selects topics to meet evolving supervisory challenges and the expectation that the international supervisory standards themselves will likewise continue to rise.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet